Identification and cytochemical immunolocalization of acetyl-CoA acetyltransferase involved in the terpenoid mevalonate pathway in Euphorbia helioscopia laticifers - Meng Wang; Dou Wang; Qing Zhang; Jia Chai; Yong Peng; Xia Cai (Botanical Studies, 2017)
Abstract Background Terpenoids, the largest class of natural products in the plant kingdom, have been widely used in medicine. The precursors of terpenoids, isoprene phosphate (IPP) and dimethylallyl pyrophosphate (DMAPP), were synthesized from a mevalonate (MVA) pathway and a 2-C-methyl-d-erythritol-4-phosphate (MEP) pathway respectively. The acetyl-CoA acetyltransferase (AACT) is the initial enzyme in MVA pathway and is considered presently to be essential for terpenoid backbone biosynthesis. The basic research on cytochemistry of terpenoid metabolic enzymes is important for understanding the mechanisms underlying major metabolic processes. However, compartmentalization of AACT in plants is in controversy. Euphorbia helioscopia L. containing laticifers in the whole plant is a famous ancient folk medicine for tumor treatment, and the terpenoid is an active ingredient. Furthermore, the laticifer cell is the main synthesizing and storing site for terpenoids. Results The gene of AACT was cloned successfully from E. helioscopia, and named as EhAACT. The EhAACT expression has no significant difference among roots, stems and leaves. However, compared with the roots and stems, the EhAACT expression level is slightly higher in leaves. In addition, EhAACT recombinant protein was expressed by procaryotic expression system and anti-EhAACT antibody was prepared, the molecular weight is about 43 kDa. Western blotting results illustrated that the EhAACT antibodies specifically recognized the endogenous proteins in E. helioscopia laticifers. At last, the subcellular localization of EhAACT in E. helioscopia laticifers was observed by using colloidal gold immune-electron microscopy. EhAACT was found to mainly distribute in the endoplasmic reticulum (ER), vacuoles originated from ER and cytosol aound vacuoles originated from ER. Conclusions As a result, we speculated that in E. helioscopia laticifers, EhAACT located in cytosol would be transferred to small vacuoles dilated from ER, and the precursors of terpenoids were synthesized in these small vacuoles, then terpenoids were further synthesized into latex particles. This result would provide theoretical basis for regulating and controlling of terpenoid biosynthesis in laticifers.